Blandfoder i automatiska mjölkningssystem - Cederholm, Marika (2014)
A totally mixed ration (TMR) is a mixture of all the necessary feed components for the cow. She will eat the exact same feed in every bite which will make the rumen pH more stable and always supply her with a constant proportion between roughage and concentrate. This will make it possible for the cow to eat more dry matter (DM) a day because the fibre requirements are fulfilled. If a part of the concentrate is given separated from the mixture it is called partly mixed rations (PMR) and is almost always used when using an automatic milking system (AMS). When using TMR and PMR it is important to have a high hygiene, be accurate when mixing the feed and to look after cows in a good and strict way. The aim of this study was to document different farms with PMR in an AMS to see which routines they have and how they are managing their production. The purpose was also to try to find a few trends of what a farm with a good production does special, if there was a possibility to make some guidelines for how to achieve a high milk yield. 11 farms were investigated and visited during the summer of 2007. 7 farms had DeLaval stations and 4 farms had Lely stations. During the visit the farmer answered a questionnaire about the farms production, choices of feed stuff and routines, but also about the philosophy around the choice PMR and AMS. To complement the questionnaire data was taken from the milking station at 9 of the farms. 5 farms had the cow traffic system Feed First, 3 farms had guided traffic and 3 farms had free cow traffic. The milk yield at the farms differed between 8300 kg ECM milk to 10500 kg. The number of feedings per day differed between 2 and 12 times, and the amount of roughage between 60 and 85 % (kg feed, not dry matter). When looking at how the milking was distributed over the day an effect of feeding was quiet clear during the day. But almost all the farms had a decline in number of milking in the after night, regardless of if they feed the animals during this period. To be able to compare the farms a high milk yield was chosen to be the most attractive thing for the farmer to achieve. This was compared to different parameters in hope of finding some statistical relations. Some parameters were not linked to a high milk yield, for example the protein or fat content in the milk. The number of feedings a day was not linked to the milk yield. Farms with a high milk yield had a shorter milking interval, a lower proportion of roughage in the PMR, a higher production goal with their mixture, a lower concentrate ration in the milking station and a high goal with the total production on the farm. The conclusion is that using PMR in an AMS will not guarantee a high and good production but it is possible to achieve it.